Therapeutic effect of auricular acupoint sticking and pressing on postoperative pain of patients with granulomatous lobular mastitis (耳穴贴压治疗肉芽肿性小叶性乳腺炎术后疼痛疗效观察) - LI Suna (李苏娜); LIU Kexin (刘可欣); CHEN Hong (陈宏) (中西医结合护理)
Objective To observe the effect of auricular acupoint sticking and pressing on postoperative pain of patients undergoing surgical treatment for granulomatous lobular mastitis (GLM). Methods Totally sixty GLM patients were randomly divided into control group and treatment group, with 30 cases in each group. All patients received routine post-operative nursing, and those in the treatment group were given auricular acupoint sticking and pressing therapy within half an hour after operation. The degree of postoperative pain was evaluated by Numerical Rating Scale(NRS) at 6 h, 24 h and 48 h after operation, and the collected data were analyzed. Results The overall rate of pain relief in the treatment group was higher than that in the control group at 24 h after surgery (83. 33% vs. 53. 33%, P＜0. 05 ). The overall rate of pain relief in the treatment group was higher than that in the control group at 48 h after surgery (93. 33% vs. 73. 33%, P＜0. 05 ). Conclusion The auricular acupoint sticking and pressing is an easy-to-operate and safe technique of Traditional Chinese Medicine, and it is effective in relief of postoperative pain in GLM patients. (目的 观察耳穴贴压治疗肉芽肿性小叶性乳腺炎术后疼痛的效果。方法 将60例肉芽肿性小叶性乳腺炎患者随机分为对照组30例和治疗组30例。两组均接受手术治疗, 对照组实施术后常规护理, 治疗组在对照组基础上, 于术后30 min内给予耳穴贴压。采用数字评分法(NRS)评估患者术后6 h、24 h和48 h疼痛程度, 评价干预效果。结果 术后24 h, 疼痛有效缓解率治疗组为83. 33%(25/30), 高于对照组的53. 33%(16/30), 差异有统计学意义(P＜0. 05)。术后48 h, 疼痛有效缓解率治疗组为93. 33%(28/30), 高于对照组的73. 33%(22/30), 差异有统计学意义(P＜0. 05)。结论 耳穴贴压能有效缓解肉芽肿性小叶性乳腺炎术后疼痛程度, 且操作简单、安全。)